THE BALANCE BETWEEN THE PROTECTION OF REFUGEES’ RIGHTS AND THE INTERESTS OF STATE SECURITY - Tsikhitatrishvili, Nino (MIGRATION POLICY AND LEGAL RESPONSES, 2025)
The subject of the research is connected to the existing complex intersection in asylum law between state security interests and refugee rights. This scholarly work will explore the importance of the right to state secret information provided by the Counterintelligence. Department and “Equality of arms” principle according to the practice established by European countries, the European Court of Human Rights, and the Court of Justice of the European Union (CJEU). At the same time, the research is connected to the principle of non-refoulement, viewed as a norm of jus cogens and within the legal framework of interference with the right mentioned above. The paper will focus on the importance of the determination of the balancing test between private and public interests, in connection with the issues about refusal on granting refugee status, cancellation, revocation and right of expulsion. This part of the paper will also discuss the existing favorable practice of the court of member countries of European Union and existing opinions in scientific literature. In addition, there will be analyzed standard of evaluation of circumstances and issue of determination of objective and subjective characteristics of action based on the approach of the countries that have strong multiple-year asylum system. The paper aims to define, through an analysis of the principle of proportionality, how the involvement in the protected right is justified by national interests in comparison with the scales of the expected threats of greater severity. Also, based on the method of comparative legal research, the paper endeavors to determine, with the consideration of state security, whether refusal to grant international protection for the person meets the criteria of proportionality with the necessity of restriction and the measures used to be reached. It should be noted that the subject to be studied in the scientific doctrine of Georgia is less researched; accordingly, considering scarce literature, the research of the indicated subject is essentially essential to advance in the protection of refugee rights, determination of expediency of the granting of status, and court practice.